The Secret of Golden Flower (Jinhua Zongzhi 金華宗旨) and Zhu Yuanyu 朱元育’s Neidan Method: Centering on the Examination of the Content of Chapter Eight, “Instruction for Rambling Without Destination (Xiaoyao Jue 逍遥訣)” - Yuria Mori (Religions)
This paper re-examines the Inner Alchemy methods found in The Secret of Golden Flower, or Taiyi Jinhua Zongzhi (太乙金華宗旨, abbreviated as JZ), a text created through fuji (spirit-writing) attributed to Lüzu (呂祖) in Changzhou 常州 during the late 17th century. Recent research has shown that Pan Yi’an (潘易庵), one of the primary editors of JZ, was, in fact, the same person as Pan Jingguan (潘靜觀), who assisted in the editing of Illuminating the Mystery of Concordance of the Three According to the Book of Changes (Cangtongqi chanyou, 参同契闡幽) and Illuminating the Mystery of Awakening the Perfection (Wuzhen pian chanyou, 悟真篇闡幽) as a disciple of Zhu Yuanyu (朱元育), the editor of these works. Meanwhile, in my recent research, I have reconstructed the Inner Alchemy methods described in these two works. (For the sake of convenience, in this discussion, I will refer to this system as the “Chanyou neidan method”, as both works include the term “Chanyou” in their titles.) Upon re-examining JZ with this framework in mind, I began to suspect that its content might be based on the Chanyou neidan method. This hypothesis is rendered highly plausible by the fact that Pan Yi’an, a key editor of JZ, was the same individual as Pan Jingguan, who assisted in the editing of the two Chanyou works. The aim of this paper is to analyze the similarities and differences between the content of JZ and the Chanyou neidan method, demonstrating that the former is indeed based on the latter. Furthermore, I intend to show that while JZ incorporates the Chanyou neidan method, it also simplifies its content significantly, making it a practical manual designed for literati (士大夫 shidafu) of the Qing dynasty to integrate Inner Alchemy into their daily lives. Additionally, although JZ was created through fuji (spirit-writing), I propose that fuji also functioned as a means for Qing-era literati to adapt Daoist cultivation practices to their own lifestyles.